Pengembangan Media Pembelajaran Berbasis Canva pada Materi Daulah Abbasiyah untuk Siswa Kelas XI Madrasah Aliyah - Saidah, Nur Aina Faizzatus; Ma'arif, Iin Baroroh (YASIN, 2025)
The advancement of digital technology demands innovation in the learning process to prevent it from becoming monotonous and disengaging. One of the key issues in the teaching of Islamic Cultural History (Sejarah Kebudayaan Islam or SKI) at the Madrasah Aliyah level, particularly on the topic of the Abbasid Dynasty (Daulah Abbasiyah) is the overreliance on lecture-based methods, which results in low student enthusiasm. This study aims to develop Canva-based learning media that is engaging, interactive, and tailored to student needs. The method used is Research and Development (R&D) with the ADDIE model, consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 26 eleventh-grade students at Madrasah Aliyah Al-Bairuny. Instruments included expert validation questionnaires and student response questionnaires. Validation results showed a score of 79% from media experts and 85% from content experts, categorized as “Appropriate.” The student trial yielded an average score of 88.6%, classified as “Very Good.” The study concludes that Canva-based learning media is effective in increasing student motivation and understanding of the Abbasid Dynasty material. The implications suggest that this media can serve as an innovative alternative for SKI learning and a reference for developing similar media in other subjects.